The relationship between English language learners' motivation and online self-regulation: A structural equation modelling approach. (August 2018) - Zheng, Chunping; Liang, Jyh-Chong; Li, Mang; Tsai, Chin-Chung
Abstract: This study presents a structural relationship model that integrates English language learners' motivation with their online self-regulation. Two questionnaires, Online Language Learning Motivation (OLLM) and Online Self-regulated English Learning (OSEL), were developed and administered to 293 Chinese university students. The results indicated that OLLM consists of five factors, namely online language learning experience, cultural interest, instrumentality-promotion, instrumentality-prevention, and others' expectations. Meanwhile, OSEL is composed of six factors: goal setting, time management, environment structuring, help seeking, task strategies, and self-evaluation. The path analysis revealed that students with a positive future image of their language learning and an intrinsic interest in English culture tended to have better self-regulatory capacity in online learning environments. In contrast, students who learn English so as to avoid negative academic results might be less motivated to carry out online self-regulated learning. Also worthy of note is the negative association between L2 learners' previous online learning experience and their online self-regulatory efforts. Learners with positive online learning experiences tended to be more flexible and independent in their self-regulatory learning process. Related pedagogical implications are discussed, such as motivating learners to visualize a successful future self, improving their inherent interest in learning English, and designing more effective online tasks.